Hermite–Hadamard-type inequalities for interval-valued preinvex functions via Riemann–Liouville fractional integrals - Sharma, Nidhi; Singh, Sanjeev Kumar; Mishra, Shashi Kant; Hamdi, Abdelouahed (Journal of inequalities and applications, 2021)
In this paper, we introduce ( h 1 , h 2 ) -preinvex interval-valued function and establish the Hermite–Hadamard inequality for preinvex interval-valued functions by using interval-valued Riemann–Liouville fractional integrals. We obtain Hermite–Hadamard-type inequalities for the product of two interval-valued functions. Further, some examples are given to confirm our theoretical results.